2008
DOI: 10.1111/j.1813-6982.2008.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Quality Performance Indicators for Home Community‐based Care Services to Orphans and Vulnerable Children

Abstract: The encouragement of care of orphans and vulnerable children by non‐profit organisations (NPOs) is a major policy response to the HIV and AIDS epidemic in South Africa. The purpose of this article is to present a quality–cost model with five performance indicators for quality and two for costs and to test these against actual performance using data collected from nine rural and urban organisations in 2004 and 2005. Six NPOs had acceptable cost but all had unacceptable quality scores; three had unacceptable cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Contrasting evidence suggests that gender and region of residence are also important predictors of poor schooling outcomes of orphan children; urban orphans appear to be more vulnerable than their urban peers (Campbell et al, 2010). Findings also show that the poorest students, and girls especially, experience disparity, therefore they should be given more opportunities to attain an education and to reach their potential, contributing to family and national health and wealth (Lingenfelter et al, 2017;Naidu et al, 2008;Jeffery et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting evidence suggests that gender and region of residence are also important predictors of poor schooling outcomes of orphan children; urban orphans appear to be more vulnerable than their urban peers (Campbell et al, 2010). Findings also show that the poorest students, and girls especially, experience disparity, therefore they should be given more opportunities to attain an education and to reach their potential, contributing to family and national health and wealth (Lingenfelter et al, 2017;Naidu et al, 2008;Jeffery et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Greater attention should be paid to the structure and content of home visiting, setting realistic targets and ensuring fidelity to the model. Further research could also help establish optimal care worker ratios (Naidu et al, 2008 ) and “dose” standards (Paulsell, Del Grosso, & Supplee, 2014 ), especially in light of evidence suggesting that beneficiaries with the highest exposure to home visiting are the most likely to show improvement (Azzi-Lessing, 2011 ; Howard & Brooks-Gunn, 2009 ; Nievar et al, 2010 ; Powell & Grantham-McGregor, 1989 ). Finally, rigorous evaluation efforts will be pivotal to assessing these programs’ progress toward their ultimate goals: improving children’s health and well-being through strategic, effective, family-centered support.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing concern that reliance on inadequately trained and compensated volunteers results in poor program quality (Sherr & Zoll, 2011 ; Schenk & Michaelis, 2010 ; Lehmann & Sanders, 2007 ). A South African study found of nine community-based home visiting programs, none met the minimum performance criteria (Naidu, Aguilera, de Beer, Netshipale, & Harris, 2008 ). There is also another concern that a reliance on volunteers – who are often as under-resourced as the families they serve – is exploitive (Desmond, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Home visiting programs vary substantially in both their design and their implementation ( Howard & Brooks-Gunn, 2009 ). Formal training and greater frequency and duration of visits have been suggested as key factors that characterize the highest quality programs ( Naidu, Aguilera, de Beer, Netshipale, & Harris, 2008 ). Similarly, prior studies have highlighted the potential importance of home visitor compensation, training, and organizational support on beneficiary outcomes ( Nyangara et al, 2009 ; Sherr & Zoll, 2011 ).…”
Section: Introductionmentioning
confidence: 99%